The Dynamic Financial Implications of the Community College Baccalaureate: An Institutional Exploration - Jeremy Wright-Kim (AERA Open, 2022)
Using generalized difference-in-difference and synthetic control modeling, this study estimates the influence of the community-college baccalaureate (CCB) on institutional finance over time and by intensity. Leveraging data spanning 19 years (1999–2017), I find no impact on overall revenue but suggestive evidence of upfront costs and slight increases in total spending post-adoption. Coupled with increased enrollment, per-full-time-equivalent (FTE) revenue and spending decrease, on average, by approximately 12% and 6%, respectively. Adoption of an additional CCB is associated with a 3% decrease in revenue and a suggestive 2% reduction in spending per FTE. Additional robustness checks suggest that these impacts may vary by state. These results suggest that institutions should consider the trade-offs in broadening access to baccalaureate-level education with the associated strain on resources. Policymakers should consider how best to financially support adoptive institutions as they work to meet student and workforce needs. Implications for policy, practice, and research are discussed.